PERSPECTIVES OF DEVELOPMENT OF SCRAP PROCESSING AT JSC «BMZ» - S. M. Borschov; V. N. Prohorenko; S. S. Vostrikov (Литьë и металлургия, 2012)
The perspectives of development of scrap processing on JSC “BMZ” which will allow to provide steel-smelting production by metal-burden of required quality are shown.